Genomic Characterization of Streptococcus suis Serotype 24 Clonal Complex 221/234 From Human Patients - Kerdsin, Anusak; Hatrongjit, Rujirat; Wongsurawat, Thidathip; Jenjaroenpun, Piroon; Chopjitt, Peechanika; Boueroy, Parichart; Fittipaldi, Nahuel; Zheng, Han; Gottschalk, Marcelo (Frontiers in Microbiology, 2021)
Streptococcus suis is a zoonotic pathogen that causes invasive infections in humans and pigs. Although S. suis serotype 2 is prevalent among patient and swine infections, other serotypes are occasionally detected in humans. Of these, serotype 24 clonal complex (CC) 221/234 are recognized as emerging clones of human infection. Genomic exploration of three S. suis serotype 24 CC221/234 strains revealed antimicrobial resistance genes, pathotyping, virulence-associated gene (VAG) profiles, minimum core genome (MCG) typing, and comparison of the genomes. Based on these analyzes, all three serotype 24 strains were MCG7-3 and should be classified in the intermediate/weakly virulent (I/WV) group. All selected serotype 24 strains were susceptible to several antibiotics including β-lactam, fluoroquinolone, and chloramphenicol. Resistance to tetracycline, macrolide, and clindamycin was observed and attributed to the genes tet(O) and erm(B). Genomic comparison revealed the strains S12X, LSS66, LS0L, LS0E, 92–4,172, and IMT40201 that had phylogenetic affinity with serotype 24 CC221/234. Analysis of 80 virulence-associated genes (VAG) showed that all three serotype 24 strains lacked 24 genes consisting of adhesin P, epf, hyl, ihk, irr, mrp, nadR, neuB, NisK/R, ofs, permease (SSU0835), rgg, revS, salK/R, sao, sly, spyM3_0908, srtBCD, srtF, srtG, SSU05_0473, virA, virB4, and virD4. Eleven specific sequences were identified in the 3 serotype 24 genomes that differed from the genomes of the representative strains of epidemic (E; SC84), highly virulent (HV; P1/7), I/WV (89–1,591), and avirulent (T15 and 05HAS68).